RHETORICAL MOVES OF ABSTRACTS: INVESTIGATING ABSTRACTS THESIS OF ENGLISH EDUCATION DEPARTMENT STUDENTS IN SURAKARTA - Karmila, Karmila; Laila, Malikatul (Jurnal Penelitian Humaniora, 2020)
Abstract in the thesis is a must, even in the journal, research article, conference, or dissertation. People could decide whether they want to continue the full content in the paper through abstract. This research aims to what extent the rhetorical structure of abstracts follows the structure of their RAs in terms of IMRD structure and what rhetorical moves writers most frequently employ in the abstract sections of the Bachelor Abstract Thesis English Education Department. Corpus data was used to do the research. The document of abstracts 40 in total and were chosen from Undergraduate degree students in English Education Department at Universitas Muhammadiyah Surakarta. The abstracts were selected randomly, and it is consists of two types of concentrations in the field of education and literature. The selected abstracts were published between 2018 to 2019. The instruments were using Hyland'sÂ  (2000) five moves to identify the selected abstracts' rhetorical structure. The result showed that most of the abstracts have a purpose (100%), then method (97,5%), and the result or product is 87,5%. The conclusion is only 22,5%, and the introduction was rarely used, it showed only 5%.